Synthesis and antibacterial activity of 1-(3-hydroxy-2-naphthoyl)-4-substituted thiosemicarbazides - (:unkn) unknown (My University, 1999)
1-(3-Hydroxy-2-naphthoyl)-4-substituted thiosemicarbazides were obtained by the addition of 3-hydroxy-2-naphthoic acid hydrazide to various isothiocyanates. The structures of the synthesized compounds were confirmed using UV and 1H-NMR spectral methods together with elemental analysis.
Keywords: Anti-Bacterial Agents; Escherichia coli; Microbial Sensitivity Tests; Staphylococcus aureus; Klebsiella; Proteus; Pseudomonas; Semicarbazides